2020
DOI: 10.1038/s41598-020-74157-y
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin Dp71ab is monoclonally expressed in human satellite cells and enhances proliferation of myoblast cells

Abstract: Dystrophin Dp71 is the smallest isoform of the DMD gene, mutations in which cause Duchenne muscular dystrophy (DMD). Dp71 has also been shown to have roles in various cellular processes. Stem cell-based therapy may be effective in treating DMD, but the inability to generate a sufficient number of stem cells remains a significant obstacle. Although Dp71 is comprised of many variants, Dp71 in satellite cells has not yet been studied. Here, the full-length Dp71 consisting of 18 exons from exons G1 to 79 was ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 40 publications
1
23
2
Order By: Relevance
“…We confirm that myotubes in culture produce high levels of Dp71, and that this capacity is retained in DMD patients with mutations upstream of the Dp71 promoter. This, and previous findings, strongly, indicate a role for Dp71 in myoblast cell proliferation and satellite cell activation [31][32][33]. This suggests that the low level of Dp71 production in DMD muscle is a secondary phenomenon related to the muscle degeneration and regeneration characteristic of DMD.…”
Section: Discussionsupporting
confidence: 79%
“…We confirm that myotubes in culture produce high levels of Dp71, and that this capacity is retained in DMD patients with mutations upstream of the Dp71 promoter. This, and previous findings, strongly, indicate a role for Dp71 in myoblast cell proliferation and satellite cell activation [31][32][33]. This suggests that the low level of Dp71 production in DMD muscle is a secondary phenomenon related to the muscle degeneration and regeneration characteristic of DMD.…”
Section: Discussionsupporting
confidence: 79%
“…Given that Dp71 dystrophin is found in undifferentiated myogenic cells [26], and that in development shorter dystrophins have been associated with proliferation and migration, and long isoforms with terminal commitment [77], we hypothesized that eliminating expression of Dp71 may exacerbate dysfunctions in myogenic cells. Surprisingly, we found that both Dmd mdx and Dmd mdx-βgeo cells had similar abnormalities and, contrary to Dp71 overexpression increasing myoblast proliferation [64], BrdU incorporation in dystrophin-null myoblasts was still significantly increased compared to WT. Interestingly, Dmd mdx myoblasts, having a point mutation in exon 23, express a significantly lower levels of Dp71 (Figure S6), whose expression is driven by a promoted located over 40 exons downstream of the mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this structural difference, Dp71ab has been shown to have different functions from Dp71 ( Marquez et al, 2003 ; Herrera-Salazar et al, 2016 ), but the functional characterization of each isoform has been hampered by the coexpression of isoforms ( Aragon et al, 2016 ; Rani et al, 2019 ). In our previous study, human Dp71ab was shown to be exclusively expressed in human satellite cells ( Farea et al, 2020 ). Moreover, we demonstrated that Dp71ab enhances myoblast proliferation ( Farea et al, 2020 ).…”
Section: Introductionmentioning
confidence: 88%
“…In our previous study, human Dp71ab was shown to be exclusively expressed in human satellite cells ( Farea et al, 2020 ). Moreover, we demonstrated that Dp71ab enhances myoblast proliferation ( Farea et al, 2020 ). Thus, Dp71ab was shown to be involved in cell proliferation.…”
Section: Introductionmentioning
confidence: 88%